Estrogen-dependent disruption of intracellular iron metabolism augments the cytotoxic effects of doxorubicin in select breast and ovarian cancer cells - Bajbouj, Khuloud (Cancer Manag Res, 2019)
Introduction: Increased iron content in cancer cells is associated with resistance to chemotherapy. Recent studies have demonstrated that estrogen (E(2)) suppresses hepcidin synthesis and enhances intracellular iron efflux. Herein, we investigated whether E(2)-driven intracellular iron efflux renders cancer cells more susceptible to doxorubicin (Dox)-induced cytotoxicity. Methods: Breast, ovarian, and liver cancer cell lines treated with E(2), Dox, or a combination of both were assessed for intracellular iron status, mitochondrial function, cell cycle, and apoptosis. Results: E(2)+Dox treatment in MCF7, SKOV3 and MDA-MB231 cells resulted in enhanced apoptosis compared with Dox-treated cells. Expression of γH2AX was significantly higher and that of survivin significantly lower in E(2)+Dox-treated cells than Dox-treated cells. At 48 hours, E(2)+Dox had induced a significant increase in the percentage of sub-G(1) apoptotic cells, increased CHK1 expression, and decreased cyclin D1, CDK4, and CDK6 expression. Ferroportin and ferritin expression was significantly higher and that of TfR1 significantly lower in E(2)+Dox-treated cells than Dox-treated cells. Intracellular iron content was significantly reduced in E(2)+Dox-treated cells at 48 hours posttreatment. Lastly, E(2)+Dox-treated cells showed higher levels of mitochondrial membrane hyperpolarization than Dox-treated cells. Conclusion: These findings suggest that E(2) disrupts intracellular iron metabolism in such a way that increases cell susceptibility to Dox-induced cytotoxicity.